The effects of MicroSource S on growth performance, fecal consistency, and postcleaning microbial load of growing-finishing pigs - S Nitikanchana; Joel M DeRouchey; J R Bergstrom; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2012)
A total of 1,245 pigs (PIC 1050 × 337, initially 106 lb) were used in a 90-d study to determine the effects of MicroSource S (DSM Nutritional Products Inc., Parsippany, NJ) and diet type on growth performance, carcass traits, fecal consistency, pen cleaning time, and postcleaning microbial load in growing-finishing pigs raised under commercial conditions. Pens of pigs were balanced by initial weight and randomly allotted to 1 of 6 dietary treatments in a completely randomized design with 25 to 26 pigs per pen and 8 replications per treatment. Treatments were arranged as a 3 × 2 factorial with main effects of MicroSource S (0, 1×, or 1.3×) and diet type (corn-soybean meal or a by-product—based diet with 30% dried distillers grains with solubles [DDGS] and 15% bakery by-product). The MicroSource S dose in the diet was 147 million cfu/g feed for the 1× level and 191 million cfu/g feed for the 1.3× level. Fecal consistency and manure buildup in each pen was scored at the end of the trial by 3 observers with the average value per pen used for analysis. Time required to wash each individual pen was also recorded. After pens were cleaned and dried, ATP (adenosine triphosphate) testing was used to measure microbial load in each pen.; Swine Day, Manhattan, KS, November 15, 2012
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-026-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1074; Swine; By-products; Enzyme fecal consistency; Microbial load; Finishing pig; Wash time